2014
DOI: 10.1089/vbz.2013.1387
|View full text |Cite
|
Sign up to set email alerts
|

Vector-Borne Agents Detected in Fleas of the Northern White-Breasted Hedgehog

Abstract: This is the first large-scale molecular investigation of fleas from a geographically widespread and highly urbanized species, the northern white-breasted hedgehog. In this study, 759 fleas (the majority were Archaeopsylla erinacei) collected from 134 hedgehogs were molecularly analyzed individually or in pools for the presence of three groups of vector-borne pathogens. All flea samples were positive for rickettsiae: In two samples (1.5%) Rickettsia helvetica and in 10% of the others a novel rickettsia genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…were reported to infect Atelerix algirus and fleas infesting hedgehogs [ 31 , 145 ]. Consistent with our results, Bartonella species were detected in A. erinacei collected from the northern white-breasted hedgehog [ 146 ]. In addition, Bartonella spp.…”
Section: Discussionsupporting
confidence: 90%
“…were reported to infect Atelerix algirus and fleas infesting hedgehogs [ 31 , 145 ]. Consistent with our results, Bartonella species were detected in A. erinacei collected from the northern white-breasted hedgehog [ 146 ]. In addition, Bartonella spp.…”
Section: Discussionsupporting
confidence: 90%
“…Fleas are capable of transmitting to humans the obligate intracellular bacterium, Rickettsia felis, that causes a typhus-like disease in humans (Perez-Osorio et al 2008). Most (96%) A. erinacei fleas were found to harbour R. felis in Germany (Gilles et al 2009), and in a recent molecular analysis of the [2009][2010] fleas from the present study, all flea samples were positive for rickettsiae, with two samples (1.5%) harbouring Rickettsia helvetica and 10% positive for a novel Rickettsia genotype (see Hornok et al 2014). Additionally, Bartonella henselae (the causative agent of cat scratch disease in humans) was detected in one A. erinacei (0.7%), and hemoplasmas of the hemofelis group were identified in seven other samples (5.2%) (Hornok et al 2014).…”
supporting
confidence: 63%
“…A study from the Netherlands showed occurrence of Rickettsia helvetica DNA in two unknown species of fleas collected from rodents (Sprong et al 2009). Furthermore, Hornok et al (2014) showed the presence of this species in two females of Archaeopsylla erinacei.…”
Section: Discussionmentioning
confidence: 95%
“…The occurrence of some species of Rickettsia was described in fleas in several European countries (Brouqui et al 2006, Parola 2011, Hornok et al 2014, Špitalská et al 2015, Radzijevskaja et al 2018, Víchová et al 2018. Four groups belong to Rickettsia: Spotted Fever Group rickettsiae (SFG) including approximately 20 species, Typhus Group (TG) with R. prowazeki and R. typhi, the ancestral group (R. canadensis and R. belli) and the transitional group (R. akari, R. felis and R. australis) (Wood andArtsob 2011, Radzijevskaja et al 2018).…”
mentioning
confidence: 99%